Effect of Dietary Cocoa Tea (Camellia ptilophylla) Supplementation on High-Fat Diet-Induced Obesity, Hepatic Steatosis, and Hyperlipidemia in Mice. (9th July 2013) - Yang, Xiao Rong; Wat, Elaine; Wang, Yan Ping; Ko, Chun Hay; Koon, Chi Man; Siu, Wing Sum; Gao, Si; Cheung, David Wing Shing; Lau, Clara Bik San; Ye, Chuang Xing; Leung, Ping Chung
Abstract : Recent studies suggested that green tea has the potential to protect against diet-induced obesity. The presence of caffeine within green tea has caused limitations. Cocoa tea ( Camellia ptilophylla ) is a naturally decaffeinated tea plant. To determine whether cocoa tea supplementation results in an improvement in high-fat diet-induced obesity, hyperlipidemia and hepatic steatosis, and whether such effects would be comparable to those of green tea extract, we studied six groups ( n = 10 ) of C57BL/6 mice that were fed with (1) normal chow (N); (2) high-fat diet (21% butterfat + 0.15% cholesterol, wt/wt) (HF); (3) a high-fat diet supplemented with 2% green tea extract (HFLG); (4) a high-fat diet supplemented with 4% green tea extract (HFHG); (5) a high-fat diet supplemented with 2% cocoa tea extract (HFLC); and (6) a high-fat diet supplemented with 4% cocoa tea extract (HFHC). From the results, 2% and 4% dietary cocoa tea supplementation caused a dose-dependent decrease in (a) body weight, (b) fat pad mass, (c) liver weight, (d) total liver lipid, (e) liver triglyceride and cholesterol, and (f) plasma lipids (triglyceride and cholesterol). These data indicate that dietary cocoa tea, being naturally decaffeinated, has a beneficial effect on high-fat diet-induced obesity, hepatomegaly, hepatic steatosis, and elevated plasma lipid levels in mice, which are comparable to green tea. The present findings have provided the proof of concept that dietary cocoa tea might be of therapeutic value and could therefore provide a safer and cost effective option for patients with diet-induced metabolic syndrome.